1991
DOI: 10.1111/j.1745-9125.1991.tb01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Drug Use, Drug Trafficking, and Other Delinquency Among Inner‐city Adolescent Males in Washington, D.C.*

Abstract: This paper examines (1) the relationship between drug involvement among inner-city youths and the commission of other kinds of crime, (2) the role of drug use in crime commission, (3) the connection between crime and drug procurement, and (4) the factors that distinguish between individuals as a function of (a) levels of involvement in drug trafficking and (b) drug usage and criminal activity.Drug use and trafficking were both related to other criminal activities; the type of drug involvement was related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
2
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 26 publications
2
54
2
2
Order By: Relevance
“…Furthermore, those studies that have examined these associations have had mixed results (Altschuler and Brounstein 1991;Hartstone and Hansen 1984;Huizinga, Menard, and Elliott 1989;Tinklenberg et al 1981). The purpose of this study was to examine the proxiThe preparation of this article was supported in part by grants from the National Institute on Drug Abuse (DA 41101 and DA/AA 03395), the National Institute on Mental Health (NIMH 50778), the Office of Juvenile Justice and Delinquency Prevention (OJJDP 96-MU-FX-0012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, those studies that have examined these associations have had mixed results (Altschuler and Brounstein 1991;Hartstone and Hansen 1984;Huizinga, Menard, and Elliott 1989;Tinklenberg et al 1981). The purpose of this study was to examine the proxiThe preparation of this article was supported in part by grants from the National Institute on Drug Abuse (DA 41101 and DA/AA 03395), the National Institute on Mental Health (NIMH 50778), the Office of Juvenile Justice and Delinquency Prevention (OJJDP 96-MU-FX-0012).…”
mentioning
confidence: 99%
“…Many adolescents reported that they actually moderated their use when they knew they were going to commit illegal acts. In a study of inner-city ninth graders, Altschuler and Brounstein (1991) found that only a minority of youth used drugs before committing any type of illegal act. Huizinga et al (1989), in a national study of adolescents, reported higher rates of acute alcohol use than drug use for all index offenses except robbery, for which the rates were equal for both substances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…En effet, au niveau individuel, ce n'est pas parce qu'un délinquant est aussi un toxicomane qu'il y a nécessai-rement un lien causal entre les phénomènes; ces deux types de déviance peuvent se développer à partir d'une série de causes communes (voir Altschuler et Brounstein, 1991 ;Brook et Cohen, 1989) 15 .…”
Section: Resultsunclassified
“…L'abondance des recherches sur la relation liant consommation de drogues et criminalité parmi la population contrevenante réelle et potentielle (voir par exemple Altschuler et Brounstein, 1991;Chaiken et Chaiken, 1990;Goldstein, 1985;Innés, 1988), frappe en regard du peu d'études empiriques sur le thème de la relation spatiale entre drogues et criminalité à travers le paysage physique de la ville. En effet, selon le postulat voulant que les marchés de drogues soient au centre de l'activité criminelle, il est surprenant de constater le peu de documentation disponible sur les analyses spatiales de la relation drogue-crime.…”
Section: Analyse Spatiale Des Crimes Commis Sur La Rue à L'intérieur unclassified